Strategi Komunikasi Pemasaran Asmaranur Modelling School Pekanbaru Melalui Media Sosial Instagram - Adinda Tasya Asova; Welly Wirman (Harmoni: Jurnal Ilmu Komunikasi dan Sosial, 2023)
Asmaranur Modeling School is a modeling school in Pekanbaru, which was founded by the owner and trainer, Irvan Asmara, on February 1 2020 under the auspices of CV. Asmaranur Persada Sejahtera. AMS Modeling School is the first modeling school that provides learning not only about the catwalk but also education in forming personality such as attitude, public speaking, personal branding, and responsibility. This research aims to find out the Marketing Communication Strategy of Asmaranur Modeling School Pekanbaru through Instagram Social Media. The method in this research used a case study with a qualitative approach and purposive techniques which included interviews, observation, documentation. The informant subjects in this research consisted of 3 informants, namely Irvan Asmara as the owner and instructor, Bima Sakti as the content creator, Wildatul Muslimah as a student who had been registered at AMS for a long time. This research uses New Media theory and the concept of The Circular Model of Some created by Regina Luttrell which has 4 stages, namely share, optimize, manage, engage. The results of this research are that Asmaranur Modeling School Pekanbaru chose the social media Instagram based on the increasing number of social media users and in accordance with Asmaranur Modeling School Pekanbaru's target market, namely young people and adults who are active on Instagram social media. Before posting content, collect photo/video ideas. Asmaranur Modeling School Pekanbaru's Instagram social media is managed directly by Irvan Asmara as the owner and trainer, easily responding to comments from followers, and making it easy to repost tagged posts from me personally, students who take part in activities at Asmaranur Modeling School Pekanbaru. To build engagement with consumers or followers, Asmaranur Modeling School Pekanbaru also creates events and sponsors other important events.